PENGENALAN APLIKASI GAME EDUKASI KAHOOT UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI PANTI ASUHAN DAARUL ALYA - Rini Nurlistiani; Suci Mutiara; Anggawidia Wibaselppa; Erland Nur Syihab (Jurnal Publika Pengabdian Masyarakat, 2023)
Learning media is very important in the world of education. Good learning media will influence the variety of teaching in the classroom and it is hoped that it can also improve student achievement. During the COVID-19 pandemic there were many interesting variations of learning that could increase students' interest and motivation in learning, both from the elementary/junior high school/high school-equivalent levels. One way is to carry out learning through interesting games that can be adapted by students in order to increase student motivation and be able to make students more interested in learning and improve their achievements. Kahoot is an internet-based learning media containing quizzes and games. In this service, an introduction to educational game-based learning is carried out at the Daarul Alya Islamic Boarding School because it is still relatively passive and is not familiar with technology as in other SD/SMP/SMA/equivalent as a form of variation in student learning. The results of the evaluation of this activity were that most students stated that kahoot was very easy to understand and highly motivated them in learning. So that in future implementation similar educational games will be carried out from various subjects to increase student motivation and achievement in the learning process.